Electricity in Central America: Paradigms, reforms and the energy trilemma. (April 2017) - Gent, Danielle; Tomei, Julia
A new global energy era is emerging, one driven by the confluence of energy security, climate politics and energy equity issues. This 'energy trilemma' is shaping the global political economy of energy, which in turn influences how decisions are made about how energy is provided—referred to as global energy governance. This article analyzes historical and contemporary developments in Central America's power sectors. This is a region that has long been an implementation space for global policy priorities, but has been overlooked by those engaging with the challenges of the energy trilemma. During the 1990s and 2000s, the statist model of energy governance gave way to a market-led model in the Central American isthmus. This led to the privatization of state-owned utilities and the promotion of a regional electricity market. During this period, the dominance of largely hydro-based renewable electricity generation diminished to be replaced by imported fossil fuel-based generation. Oil price increases during the early 2000s highlighted the region's dependence on imports, with some countries turning to energy rationing. Increasingly interventionist state policies, which now seek to reduce oil dependence, improve energy efficiency and expand access to electricity, are being pursued in the region. This interventionist turn reflects the pressures of the energy trilemma, although energy security, particularly the need to reduce dependence on imported oil, remains the most important driver.